A clinical test examination procedure to identify knee compartment overloading: A reliability and validity study using SPECT-CT as reference. (July 2021) - Lutz, Nathanael; Zuckerman, Silvia; Seel, François; Ott-Senn, Yvonne; Rogan, Slavko; Rasch, Helmut
Abstract: Background: Mechanical forces and joint misalignment are considered risk factors for the development of knee osteoarthritis (KOA). Early detection of KOA and distinction between lateral and medial compartment overloading (CO), might be important to inform appropriate preventative interventions. This study evaluated reliability and validity of a test battery consisting of ten clinical tests to predict knee CO. Methods: Independent observers examined 30 participants with symptoms of KOA. Inter-rater reliability of the ten tests, as well as the anticipated CO based on the whole test battery, was determined. All participants received a SPECT-CT, which served as reference standard for CO. The agreement for CO between SPECT-CT and clinical examination was assessed to determine criterion validity. Results: The Kappa coefficients ( k ) for the ten individual clinical tests ranged from 0.19 to 0.80. The k for determining CO was 0.52 (95% CI = 0.28–0.76). The agreement for CO between SPECT-CT and clinical examination (i.e. criterion validity) yielded a k of 0.26 (95% CI = −0.06 - 0.58). Logistic regression indicated that valgus alignment was strongly related with lateral CO. No other relationships were found between individual tests and CO. Conclusion: Accurate measurement of frontal plane knee angle is important to determine CO. This particular test yielded good reliability, but low validity. Reliability of the nine remaining clinical tests was fair to moderate. Criterion validity of the clinical examination to predict CO was low. Therefore, this test battery in its current form cannot be used in practice to determine CO.